Mechanisms for the prevention of adolescent intimate partner violence: A realist review of interventions in low- and middle-income countries - Hattie Lowe; Joanna Dobbin; Ligia Kiss; Joelle Mak; Jenevieve Mannell; Daniella Watson; Delanjathan Devakumar (Public Library of Science (PLoS), 2022)
Adolescent girls are among those at the greatest risk of experiencing intimate partner violence (IPV). Despite adolescence being widely regarded as a window of opportunity to influence attitudes and behaviours related to gender equality, evidence on what works to prevent IPV at this critical stage is limited outside of high-income, school-based settings. Even less is understood about the mechanisms of change in these interventions. We conducted a realist review of primary prevention interventions for adolescent IPV in low- and middle-income countries (LMICs) to synthesise evidence on how they work, for whom, and under which circumstances. The review took place in four iterative stages: 1) exploratory scoping, 2) developing initial programme theory, 3) systematic database search, screening and extraction, and 4) purposive searching and refinement of programme theory. We identified eleven adolescent IPV prevention interventions in LMICs, most of which demonstrated a positive impact on IPV experience and/or perpetration (n = 10). Most interventions (n = 9) implemented school- or community-based interactive peer-group education to transform attitudes and norms around gender and relationships for behaviour change. The central mechanism of change related to gender transformative content prompting adolescents to critically reflect on their attitudes and relationships, leading to a reconceptualisation of their values and beliefs. This central mechanism was supported by two secondary implementation mechanisms: 1) the design and delivery of interventions: interactive, age-appropriate education delivered in peer-groups provided adolescents a safe space to engage with content and build communication skills, and 2) the target group: social norms interventions targeting the wider community created enabling environments supportive of individual change. This review highlights the immense potential of gender transformative interventions during the critical period of adolescence for IPV prevention. Future interventions should consider the broader drivers of adolescent IPV and ensure intersectionality informed approaches to maximise their potential to capitalise on this window of opportunity.